Benefits of Yoga on IL-6: Findings from a Randomized Controlled Trial of Yoga for Depression - Nugent, Nicole R.; Brick, Leslie; Armey, Michael F.; Tyrka, Audrey R.; Ridout, Kathryn K.; Uebelacker, Lisa A. (Behavioral medicine (Washington, D.C.), 2021)
The present research sought to examine whether hatha yoga, implemented as an adjunctive intervention for major depression, influences markers of inflammation. A subset of 84 participants who were enrolled in a randomized controlled trial (RCT) of hatha yoga vs. health education control provided blood samples at baseline (pre-treatment) and at 3-(during treatment) and 10-week (end of treatment) follow-up visits. To be eligible for the RCT, participants met criteria for a current or recent (past two years) major depressive episode, had current elevated depression symptoms, and current antidepressant medication use. Venous blood was drawn between 2 and 6 pm and following at least one hour of fasting, and inflammatory markers (IL-6, CRP, and TNF-α) were assayed. Effects of participation in yoga relative to health education on inflammatory markers over time were examined with latent growth analyses. We observed a significant reduction in IL-6 concentrations in the yoga treatment group relative to the health education control group as demonstrated by a negative interaction between treatment group and slope of IL-6. TNF-α and CRP did not evidence significant interactions of treatment group by mean slope or intercept. In addition to the benefits of hatha yoga as an adjunctive intervention for individuals who have shown inadequate response to antidepressant medications, our findings point to possible benefits of yoga on IL-6 in depressed populations. Further research is needed to explore the effects of hatha yoga on immune function over time.